Heavy metal adsorbent using cellulose-chitosan beads derived from waste resources and manufacturing method thereof

KR1020260123866APending Publication Date: 2026-08-14KYUNGPOOK NAT UNIV IND ACADEMIC COOP FOUND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250016134
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2026-08-14

Smart Images

  • Figure PAT00008_ABST
    Figure PAT00008_ABST
Patent Text Reader

Abstract

The present invention relates to a heavy metal adsorbent using waste resource-based cellulose-chitosan beads and a method for manufacturing the same. More specifically, it relates to a method for manufacturing cellulose-chitosan beads capable of adsorbing heavy metal substances by recycling cigarette butts and seashells to extract cellulose and chitosan and combining them.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a heavy metal adsorbent using waste resource-based cellulose-chitosan beads. Background Technology

[0003] The discharge of heavy metals or active heavy metal components from sewage, landfill leachate, and various industrial wastewaters is rapidly increasing, and if heavy metals infiltrate groundwater through the soil, they can have fatal effects.

[0004] Adsorption processes are widely used to remove heavy metals contained in sewage, landfill leachate, and various types of industrial wastewater. Adsorption processes have the advantage of being relatively simple and capable of effectively removing various pollutants from aqueous solutions or industrial wastewater. Generally, adsorbents used in wastewater treatment include clay minerals, zeolites, oxides, biopolymers, and materials modified from them; research utilizing these materials has been very active over the past few years. In particular, low-cost adsorbents—specifically those derived from bio-adsorbents, agricultural byproducts, and industrial waste—have recently emerged as new alternatives, and their application in wastewater treatment or the development of products utilizing them is underway.

[0005] However, for safety reasons, the adsorbents used in drinking water treatment are still limited to activated carbon and oxidation adsorbents, despite their high cost and / or environmental impact.

[0006] Adsorbents used in adsorption processes must have high adsorption efficiency and be renewable materials to minimize environmental impact, and pretreatment for use must be inexpensive and simple.

[0007] Accordingly, the inventors completed the present invention by developing waste resource-based cellulose-chitosan beads capable of simultaneously solving waste resource recycling and heavy metal contamination. Prior art literature

[0009] Republic of Korea Registered Patent No. 10-1915730 The problem to be solved

[0010] The present invention provides a method for manufacturing cellulose-chitosan beads capable of adsorbing heavy metal substances, prepared by synthesizing chitosan extracted from seashell waste and cellulose obtained by converting cellulose acetate extracted from cigarette butts.

[0011] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0013] To achieve the above objective, the present invention provides a method for manufacturing cellulose-chitosan heavy metal beads, characterized by comprising the steps of: extracting chitosan from a seashell; separating and washing a cigarette filter from a cigarette butt; extracting cellulose acetate from the washed cigarette filter; converting the cellulose acetate into cellulose; and mixing the chitosan and the cellulose to produce cellulose-chitosan beads.

[0014] The step of extracting chitosan from the above shell may include: a step of crushing the shell; a step of placing the crushed shell into a hydrochloric acid solution with a concentration of 2 to 10% and reacting it for 22 to 26 hours, followed by washing; a step of placing the washed shell into a sodium hydroxide solution with a concentration of 2 to 10% and reacting it at 80 to 100°C for 3 to 7 hours to remove protein; a step of heating and cooling the shell from which protein has been removed while refluxing it with ethanol for 4 to 8 hours to separate chitin; and a step of placing the separated chitin into a sodium hydroxide solution with a concentration of 45 to 55% and extracting chitosan through a deacetylation reaction at 80 to 100°C for 10 to 14 hours.

[0015] The step of separating and washing the cigarette filter from the cigarette butt may include: the step of separating the cigarette filter from the cigarette butt; the first stirring step of placing the cigarette filter into a 0.3 to 0.7 M NaCl aqueous solution and stirring it 1 to 5 times at intervals of 10 to 50 minutes at a speed of 100 to 300 rpm at room temperature; the second stirring step of placing the cigarette filter completed in the first stirring step into ethanol and stirring it for 2 to 6 hours at a speed of 300 to 500 rpm at 40 to 60 ℃; and the third stirring step of placing the cigarette filter completed in the second stirring step into ether and stirring it 1 to 5 times at intervals of 10 to 50 minutes at a speed of 300 to 500 rpm at room temperature.

[0016] The step of extracting cellulose acetate from the washed cigarette filter may include: mixing acetone and water with the washed cigarette filter to form a precipitate; separating the formed precipitate and drying it at 40 to 50°C for 22 to 26 hours; and pulverizing the dried precipitate to produce cellulose acetate in powder form.

[0017] The step of converting the cellulose acetate into cellulose may include: a step of adding the cellulose acetate to a 0.3 to 0.7 M sodium hydroxide solution and reacting it at 70 to 80 ℃ at a speed of 600 to 800 rpm for 1 to 3 hours; a step of cooling the mixture after the reaction and neutralizing it with HCl to convert the cellulose acetate into cellulose; a step of performing dialysis on the solution in which the cellulose has been formed; a step of freezing the solution after the dialysis is completed; and a step of drying the frozen solution to produce cellulose in a powdered state.

[0018] The step of preparing cellulose-chitosan beads by mixing the chitosan and the cellulose may include: adding the chitosan to 1 to 5% acetic acid; mixing the chitosan added to the acetic acid at 60 to 80°C at a speed of 100 to 300 rpm for 5 to 7 hours; adding the cellulose to the mixed chitosan solution and mixing at room temperature at a speed of 100 to 300 rpm for 5 to 7 hours; injecting the chitosan solution mixed with cellulose into a sodium hydroxide solution as a droplet to prepare cellulose-chitosan hydrogel beads; and curing the cellulose-chitosan hydrogel beads by stirring them in the sodium hydroxide solution.

[0019] In addition, the present invention provides cellulose-chitosan beads characterized by being manufactured by the above-described manufacturing method.

[0020] In addition, the present invention provides a heavy metal adsorbent comprising the above-mentioned cellulose-chitosan beads.

[0021] The above heavy metal adsorbent is Cu 2+ , Pb 2+ , Cd 2+ , Ag + , Ni 2+ and Zn 2+It can adsorb one or more metal ions selected from the group consisting of Effects of the invention

[0023] By means of the solution to the above problem, the present invention can provide an environmentally friendly heavy metal adsorbent and a method for manufacturing the same by recycling waste resources.

[0024] In addition, according to the method for manufacturing a heavy metal adsorbent of the present invention, environmental pollution can be reduced through waste resource recovery.

[0025] In addition, the method for manufacturing a heavy metal adsorbent according to the present invention can be extended and utilized in various industrial fields requiring heavy metal removal, such as wastewater treatment and industrial waste treatment.

[0026] The effects of the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art from the description in the claims. Brief explanation of the drawing

[0028] Figure 1 shows chitosan extracted from a seashell in one embodiment of the present invention. Figure 2 shows cellulose acetate extracted from a cigarette filter separated from a cigarette butt in one embodiment of the present invention. FIG. 3 shows membrane tubing dialysis used in the step of converting cellulose acetate into cellulose in one embodiment of the present invention. Figure 4 shows cellulose-chitosan beads prepared in one embodiment of the present invention. Specific details for implementing the invention

[0029] The terms used in this invention have been selected based on currently widely used general terms, taking into account their functions within the invention; however, these terms may vary depending on the intent of those skilled in the art, case law, the emergence of new technologies, etc. Additionally, in specific cases, terms have been arbitrarily selected by the applicant, and in such cases, their meanings will be described in detail in the relevant description of the invention. Therefore, the terms used in this invention should be defined not merely by their names, but based on their meanings and the overall content of the invention.

[0030] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.

[0031] When a part of a specification is described as “comprising” a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0032] Embodiments of the present invention are described below with reference to the attached drawings so that those skilled in the art can easily implement them. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0034] The present invention will be described in detail below.

[0036] The present invention provides a method for manufacturing cellulose-chitosan beads, characterized by comprising the steps of: extracting chitosan from a seashell; separating and washing a cigarette filter from a cigarette butt; extracting cellulose acetate from the washed cigarette filter; converting the cellulose acetate into cellulose; and mixing the chitosan and the cellulose to produce cellulose-chitosan beads.

[0037] First, a step to extract chitosan from seashells can be performed.

[0038] The step of extracting chitosan from the above shell may include: a step of crushing the shell; a step of placing the crushed shell into a hydrochloric acid solution with a concentration of 2 to 10% and reacting it for 22 to 26 hours, followed by washing; a step of placing the washed shell into a sodium hydroxide solution with a concentration of 2 to 10% and reacting it at 80 to 100°C for 3 to 7 hours to remove protein; a step of heating and cooling the shell from which protein has been removed while refluxing it with ethanol for 4 to 8 hours to separate chitin; and a step of placing the separated chitin into a sodium hydroxide solution with a concentration of 45 to 55% and extracting chitosan through a deacetylation reaction at 80 to 100°C for 10 to 14 hours.

[0039] After the step of extracting chitosan through the above deacetylation reaction, a step of washing the extracted chitosan may be further included. The step of washing the chitosan may be performed using distilled water, and the pH may be 7 to 8. The step of washing the chitosan is essential for increasing the purity of the chitosan and is a very important step that has a significant impact on the quality of the final product.

[0040] After the step of washing the extracted chitosan, the method may further include the step of drying and grinding the washed chitosan.

[0041] Next, the step of separating the cigarette filter from the cigarette butt and washing it can be performed.

[0042] The step of separating and washing the cigarette filter from the cigarette butt may include: the step of separating the cigarette filter from the cigarette butt; the first stirring step of placing the cigarette filter into a 0.3 to 0.7 M NaCl aqueous solution and stirring it 1 to 5 times at intervals of 10 to 50 minutes at a speed of 100 to 300 rpm at room temperature; the second stirring step of placing the cigarette filter completed in the first stirring step into ethanol and stirring it for 2 to 6 hours at a speed of 300 to 500 rpm at 40 to 60 ℃; and the third stirring step of placing the cigarette filter completed in the second stirring step into ether and stirring it 1 to 5 times at intervals of 10 to 50 minutes at a speed of 300 to 500 rpm at room temperature.

[0043] Next, a step of extracting cellulose acetate from the washed cigarette filter can be performed.

[0044] The step of extracting cellulose acetate from the washed cigarette filter may include: mixing acetone and water with the washed cigarette filter to form a precipitate; separating the formed precipitate and drying it at 40 to 50°C for 22 to 26 hours; and pulverizing the dried precipitate to produce cellulose acetate in powder form.

[0045] Next, a step to convert cellulose acetate into cellulose can be performed.

[0046] The step of converting the cellulose acetate into cellulose may include: a step of adding the cellulose acetate to a 0.3 to 0.7 M sodium hydroxide solution and reacting it at 70 to 80 ℃ at a speed of 600 to 800 rpm for 1 to 3 hours; a step of cooling the mixture after the reaction and neutralizing it with HCl to convert the cellulose acetate into cellulose; a step of performing dialysis on the solution in which the cellulose has been formed; a step of freezing the solution after the dialysis is completed; and a step of drying the frozen solution to produce cellulose in a powdered state.

[0047] In the step of converting the cellulose acetate into cellulose by cooling the mixture after the above reaction and neutralizing it with HCl, NaCl may be formed during the neutralization with HCl. Since the formed NaCl may affect the heavy metal adsorption performance, a step of performing dialysis to separate the NaCl and cellulose may be performed.

[0048] The step of performing dialysis on the cellulose-formed solution can be performed by placing the cellulose-formed solution into a membrane tubing, sealing it, connecting a Falcon tube to the tubing, and floating it in a beaker filled with distilled water to perform dialysis using osmotic pressure. In this dialysis method, the larger cellulose particles among the cellulose and NaCl are blocked by a semipermeable membrane, while NaCl dissociates in the solution phase to form smaller NaCl particles. + Ions and Cl - This utilizes the principle that ions can pass through a semipermeable membrane to separate the aforementioned NaCl and cellulose; due to this principle, NaCl in the solution inside the membrane tubing creates a concentration difference with the distilled water outside the membrane tubing, causing the distilled water to move from the outside into the membrane tubing due to osmotic pressure, and Na + Ions and Cl -As ions move outward, NaCl present in the solution can be separated from the cellulose. As a result, only cellulose from which NaCl has been removed remains inside the membrane tubing.

[0049] The step of performing dialysis on the solution in which the cellulose is formed may be performed by exchanging the distilled water at intervals of 2 to 6 hours for 60 to 70 hours. Preferably, the distilled water may be exchanged at intervals of 2 to 4 hours for 24 hours, and then exchanged at intervals of 6 hours for 36 hours to perform dialysis, but is not limited thereto. The NaCl can be removed through the dialysis step.

[0050] The step of freezing the solution after the dialysis is completed can be performed using liquid nitrogen. After freezing using liquid nitrogen, the solution is stored in an ultra-low temperature refrigerator to be completely frozen, and then dried using a freeze filter to finally obtain dried cellulose in a powder state from which NaCl has been removed.

[0051] Next, the step of manufacturing cellulose-chitosan beads by mixing the chitosan and the cellulose can be performed.

[0052] The step of preparing cellulose-chitosan beads by mixing the chitosan and the cellulose may include: adding the chitosan to 1 to 5% acetic acid; mixing the chitosan added to the acetic acid at 60 to 80°C at a speed of 100 to 300 rpm for 5 to 7 hours; adding the cellulose to the mixed chitosan solution and mixing at room temperature at a speed of 100 to 300 rpm for 5 to 7 hours; injecting the chitosan solution mixed with cellulose into a sodium hydroxide solution as a droplet to prepare cellulose-chitosan hydrogel beads; and curing the cellulose-chitosan hydrogel beads by stirring them in the sodium hydroxide solution.

[0053] The step of curing the cellulose-chitosan hydrogel beads by stirring in the sodium hydroxide solution can be performed by curing the cellulose-chitosan hydrogel beads by stirring in the sodium hydroxide solution for 10 to 14 hours.

[0054] After the step of curing the cellulose-chitosan hydrogel beads by stirring them in the sodium hydroxide solution, the method may further include the step of separating the cured cellulose-chitosan hydrogel beads from the sodium hydroxide and washing them with DI water until the pH of the solution becomes the same as that of pure DI water.

[0055] In addition, the present invention provides cellulose-chitosan beads characterized by being manufactured by the above-described manufacturing method.

[0056] In addition, the present invention provides a heavy metal adsorbent comprising the above-mentioned cellulose-chitosan beads.

[0057] The above heavy metal adsorbent is Cu 2+ , Pb 2+ , Cd 2+ , Ag + , Ni 2+ and Zn 2+It can adsorb one or more metal ions selected from the group consisting of

[0059] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0061] <Example> Preparation of Cellulose-Chitosan Beads

[0062] 1. Chitosan extraction

[0063] After crushing the clam shells using a mortar and pestle, the crushed shells were placed in a beaker and soaked in a 5% hydrochloric acid solution for 24 hours to dissolve the calcium carbonate. Subsequently, the shells were thoroughly washed with distilled water to remove impurities. After washing, the shells were placed in a 5% sodium hydroxide solution in a constant temperature bath at 90°C for more than 5 hours. To remove pigments, the shells were heated and cooled for 6 hours while refluxing with ethanol (95%) using a reflux condenser (substitute) to separate the chitin. The obtained chitin was placed in a sodium hydroxide (50%) solution and kept in a constant temperature bath at 90°C for 12 hours, during which deacetylation occurred to produce chitosan (Fig. 1). To confirm whether the obtained product was chitosan rather than chitin, it was dissolved in acetic acid (1 wt%) for verification.

[0064] 2. Cleaning cigarette filters

[0065] After separating the cigarette filter from the cigarette, 200 ml of 0.5 M NaCl aqueous solution was added enough to submerge the cigarette filter, and the mixture was stirred (at room temperature, 200 rpm, 3 times at 30-minute intervals). The filter stirred in the NaCl aqueous solution was removed, placed in 200 ml of ethanol, and stirred (at 50°C, 400 rpm, for 4 hours). Afterward, the filter stirred in the ethanol was placed in 100 ml of ether and stirred (at room temperature, 400 rpm, 2 times at 30-minute intervals).

[0066] 3. Cellulose Acetate Extraction

[0067] 200 ml of acetone and 200 ml of water were added to a washed cigarette filter. The white precipitate formed in the solution was removed using tongs. The precipitate was placed in a beaker and dried in a dryer (40-50°C, 24 hours). The dried precipitate was powdered using a mortar and pestle to obtain powdered cellulose acetate as shown in Fig. 2.

[0068] 4. Convert cellulose acetate to cellulose

[0069] 400 mL of 0.5 M sodium hydroxide (NaOH) solution was prepared in a volumetric flask or graduated cylinder. 10 g of cellulose acetate was added to 400 mL of the 0.5 M NaOH solution and reacted in a glass flask. During this process, the reaction temperature was maintained at 75°C using a hot plate. The mixed solution, equipped with a magnetic bar, was placed in a magnetic stirrer, and the reaction was carried out for approximately 2 hours with a stirring speed set to 700 rpm. This allowed the ester bonds to be hydrolyzed by the strong alkali to produce sodium acetate and cellulose. After the reaction, the mixture was cooled, and the solution, originally at pH 13.28, was neutralized with HCl to pH 6.23 to convert it into cellulose. The solution contained cellulose and NaCl formed through neutralization. Since NaCl can affect heavy metal adsorption performance, the reaction-completed solution was placed in a membrane tubing and sealed to separate cellulose and NaCl from the resulting solution. The tubing was then connected to a Falcon tube and floated in a beaker filled with distilled water to perform dialysis using osmotic pressure (Fig. 3). During the dialysis process, distilled water was exchanged at intervals of 2 to 4 hours on the first day, and at 6-hour intervals starting from the second day. This process was repeated for a total of 2.5 days. After completing dialysis, the solution inside the membrane tubing, from which all NaCl had been filtered, was transferred to a Falcon tube and frozen using liquid nitrogen. After freezing, the solution was stored in an ultra-low temperature refrigerator for one day to ensure complete freezing, and then dried using a freeze filter to finally remove NaCl and obtain dried cellulose in powder form.

[0070] 5. Manufacture of Cellulose-Chitosan Beads

[0071] 2 g of chitosan flakes were added to 100 mL of 2% (w / w) acetic acid in a beaker. The contents of the beaker were mixed on a hot plate stirrer at 70°C and 200 rpm for 6 hours. 2 g of cellulose was added to the chitosan solution and mixed on a stirrer at room temperature at 200 rpm for 6 hours. The mixed solution was injected droplets into a 1 M NaOH solution using a vibrating nozzle system. The cellulose-chitosan hydrogel beads were cured by slowly stirring in the NaOH solution for an additional 12 hours. The cured beads were separated from the NaOH solution. After washing with DI water until the solution pH was equal to that of pure DI water, the beads were stored in DI water. The prepared cellulose-chitosan beads are shown in Figure 4.

[0073] <Experimental Example> Experiment on the heavy metal (Cu) adsorption ability of cellulose-chitosan beads

[0074] We investigated whether the manufactured cellulose-chitosan beads have the ability to adsorb heavy metals (copper). The materials required for this include the manufactured cellulose-chitosan beads, copper, and an orbital shaker.

[0075] A copper solution at a concentration of 32 ppm was injected into a Falcon tube containing cellulose-chitosan beads, and the mixture was continuously mixed in an orbital shaker for 3 days to allow the beads to adsorb copper. An ICP machine was used to accurately determine whether the cellulose-chitosan beads successfully adsorbed copper.

[0076] As a result of analyzing the concentration of copper sulfate (CuSO4·5H2O) in an aqueous solution using an inductively coupled plasma spectroscopy (ICP-OES), 32.01 ppm was measured in the control group (BLK), and the concentration after using the beads (SA1) was found to be 2.814 ppm. Through this, it was confirmed that the adsorption efficiency of the cellulose-chitosan beads according to the present invention reached 91.2%. Generally, the copper adsorption efficiency of chitosan-based adsorbents is at the level of 80–90%, and some high-performance adsorbents record an efficiency of over 95%. Through this, it was confirmed that the copper adsorption performance of the cellulose-chitosan beads according to the present invention is very high.

[0077] <Calculation of Adsorption Efficiency>

[0078]

[0079]

[0080]

[0081]

[0083] Specific embodiments of the present invention have been examined so far. Those skilled in the art will understand that the present invention may be embodied in modified forms without departing from the essential characteristics of the invention. Therefore, the disclosed embodiments should be considered in an illustrative rather than a restrictive sense. The scope of the present invention is defined by the claims, not by the foregoing description, and all variations within the scope of equivalents should be interpreted as being included in the present invention.

Claims

Claim 1 A method for manufacturing cellulose-chitosan beads, characterized by comprising: a step of extracting chitosan from a seashell; a step of separating and washing a cigarette filter from a cigarette butt; a step of extracting cellulose acetate from the washed cigarette filter; a step of converting the cellulose acetate into cellulose; and a step of mixing the chitosan and the cellulose to produce cellulose-chitosan beads. Claim 2 A method for manufacturing cellulose-chitosan beads according to claim 1, wherein the step of extracting chitosan from the shell comprises: a step of crushing the shell; a step of placing the crushed shell in a hydrochloric acid solution with a concentration of 2 to 10% and reacting it for 22 to 26 hours, followed by washing; a step of placing the washed shell in a sodium hydroxide solution with a concentration of 2 to 10% and reacting it at 80 to 100°C for 3 to 7 hours to remove protein; a step of heating and cooling the shell from which protein has been removed while refluxing it with ethanol for 4 to 8 hours to separate chitin; and a step of placing the separated chitin in a sodium hydroxide solution with a concentration of 45 to 55% and extracting chitosan through a deacetylation reaction at 80 to 100°C for 10 to 14 hours. Claim 3 A method for manufacturing cellulose-chitosan beads according to claim 1, wherein the step of separating and washing a cigarette filter from a cigarette butt comprises: a step of separating the cigarette filter from the cigarette butt; a first stirring step of placing the cigarette filter in an aqueous solution of 0.3 to 0.7 M NaCl and stirring 1 to 5 times at intervals of 10 to 50 minutes at a speed of 100 to 300 rpm at room temperature; a second stirring step of placing the cigarette filter completed in the first stirring step into ethanol and stirring for 2 to 6 hours at a speed of 300 to 500 rpm at 40 to 60 ℃; and a third stirring step of placing the cigarette filter completed in the second stirring step into ether and stirring 1 to 5 times at intervals of 10 to 50 minutes at a speed of 300 to 500 rpm at room temperature. Claim 4 A method for manufacturing cellulose-chitosan beads according to claim 1, wherein the step of extracting cellulose acetate from the washed cigarette filter comprises: a step of mixing acetone and water with the washed cigarette filter to form a precipitate; a step of separating the formed precipitate and drying it at 40 to 50 ℃ for 22 to 26 hours; and a step of pulverizing the dried precipitate to produce cellulose acetate in powder form. Claim 5 A method for manufacturing cellulose-chitosan beads according to claim 1, wherein the step of converting the cellulose acetate into cellulose comprises: a step of adding the cellulose acetate to a 0.3 to 0.7 M sodium hydroxide solution and reacting it at 70 to 80 ℃ at a speed of 600 to 800 rpm for 1 to 3 hours; a step of cooling the mixture after the reaction and neutralizing it with HCl to convert the cellulose acetate into cellulose; a step of performing dialysis on the solution in which the cellulose is formed; a step of freezing the solution after the dialysis is completed; and a step of drying the frozen solution to produce cellulose in a powdered state. Claim 6 A method for manufacturing cellulose-chitosan beads according to claim 1, wherein the step of mixing the chitosan and the cellulose to produce cellulose-chitosan beads comprises: adding the chitosan to 1 to 5% acetic acid; mixing the chitosan added to the acetic acid at 60 to 80 ℃ at a speed of 100 to 300 rpm for 5 to 7 hours; adding the cellulose to the mixed chitosan solution and mixing at room temperature at a speed of 100 to 300 rpm for 5 to 7 hours; injecting the chitosan solution mixed with cellulose into a sodium hydroxide solution as a droplet to produce cellulose-chitosan hydrogel beads; and curing the cellulose-chitosan hydrogel beads by stirring them in the sodium hydroxide solution. Claim 7 Cellulose-chitosan beads characterized by being manufactured by the manufacturing method of claim 1. Claim 8 A heavy metal adsorbent comprising the cellulose-chitosan beads of claim 7. Claim 9 In claim 8, the above heavy metal adsorbent is Cu 2+ , Pb 2+ , Cd 2+ , Ag + , Ni 2+ and Zn 2+ A heavy metal adsorbent characterized by adsorbing one or more metal ions selected from the group consisting of